The effect of intradialytic exercise on dialysis patient survival: a randomized controlled trial - Mohammad Ali Tabibi; Bobby Cheema; Nasrin Salimian; Hugo de Luca Corrêa; Saghar Ahmadi (BMC Nephrology, 2023)
Abstract Background Patients with kidney failure have a high mortality rate. This study aimed to evaluate the effect of intradialytic exercise on survival in patients receiving hemodialysis (HD). Methods In this randomized controlled trial conducted in a HD center in Iran, adult patients receiving chronic HD were randomized to intradialytic exercise (60 min) in the second hour of thrice weekly dialysis for 6 months (intervention) or no intradialytic exercise (control). The primary outcome was survival rate at 12 months. Secondary outcomes were serum albumin, hemoglobin, hematocrit, red blood cell count, serum calcium, serum phosphorous, parathyroid hormone, physical function (6-min walk test) and nutritional status (Geriatric Nutritional Risk Index) during the first 6 months. The trial follow-up period was 12 months. Results The study included 74 participants (44 males) with an age average of 64 ± 12 years old and a dialysis history of 27 ± 12 months, randomized to intervention (n = 37) or control (n = 37). Compared with controls, 1-year survival was higher in the intervention group (94% vs 73%, P = 0.01). The hazard ratio in univariate analysis in intervention group was 0.17 (95% CI 0.04–0.8; P = 0.02) compared to that in control group. During the 6-month intervention period, significant between-group changes were observed in all secondary outcomes between the intervention and control groups. Conclusion Intradialytic exercise performed for at least 60 min during thrice weekly dialysis sessions improves survival in adult patients receiving HD. Trial registration ClinicalTrials.gov Identifier: NCT04898608. Retrospectively registered on 24/05/2021. Registered trial name: The Effect of Intradialytic Exercise on Dialysis Patients Survival.